Educational Intervention and the Provision of Separate Waste Bins as an Effort to Improve Environmental Care Behavior in the Community - Nani Supriyatni; Suryadi M. Ali; Karmila Fataruba; Bartol; Jenifer Pricillia Nona; Verawati Liambana (JURNAL SAINS SOSIAL DAN HUMANIORA (JSSH), 2025)
The Mafututu sub-district, located in a coastal and island area, has different geographical conditions compared to mainland areas, requiring a more participatory waste management approach supported by facilities easily accessible to the community. Initial findings indicate that the area does not yet have Temporary Waste Disposal Sites (TPS), so some residents are still dumping waste into the sea, rivers, and barangka. This situation leads to low public understanding of waste types and sorting, which impacts the sub-optimal waste management efforts in the environment. This service activity aims to assess the effectiveness of outreach in increasing community knowledge regarding waste management. The program will be held at Mafututu Village, Tidore City, on Friday, August 8, 2025. The sample size for the activity was 71 people. The intervention was carried out in several stages: preparation, health education implementation, and knowledge evaluation using pre-test and post-test questionnaires. Data analysis was performed using the paired t-test statistical test. The results of the activity showed that the average knowledge of respondents before the health education was 75.98 (SD 17.27) and increased to 89.02 (SD 11.27) after the intervention. The Paired Samples Test produced a p-value of 0.000, indicating a significant difference between knowledge before and after the health education, with an increase of 13.04 times. These findings indicate that extension activities are effective in improving public understanding of segregated waste management. Therefore, community-based environmental education can be a strategic approach to promote environmentally friendly behavior and support more sustainable waste management at the community level.